Criação de e-book como ferramenta de apoio à aprendizagem no ensino superior: uma análise dos elementos gráficos do design - Barros, Davidson Lima (2016)
In recent decades Distance Education (DE) has proven an important tool to meet the needs of the information society and knowledge. For this, it has made constant use of online education to achieve more effectively a larger number of people. In this context, the aim of this study is to analyze how the graphic elements of design are being structured in the creation of E-books in Virtual Learning Environments in education distance mode in Maranhão. Therefore, it is important to recognize these elements and how they are applied, and to investigate the role of the graphic designer in interdisciplinary teams responsible for teaching materials for distance learning. To achieve this goal is adopted as a methodological procedure exploratory qualitative research, which uses the systematic literature review. From this research, it will be identified which are the professionals involved and how they are being planned and developed the graphic elements of e-books in distance education projects from the design perspective.